Programa de juegos cooperativos para mejorar la convivencia escolar en los estudiantes de quinto grado de primaria, Trujillo, 2019 - Agreda Aurora, Karen Jackeline (2021)
The purpose of this research work was to determine to what extent the application of the _x000D_ Cooperative Games Program improves school coexistence in fifth grade students of the _x000D_ educational institution n. 81017 “Santa Edelmira”, Trujillo, 2019. For which the quasi experimental design was used. The sample consisted of 53 students. The School Coexistence _x000D_ Questionnaire, which consisted of 50 items, was considered as a data collection instrument. The _x000D_ program had 16 cooperative games that lasted approximately three months. It was applied as a _x000D_ test of non-parametric Mann-Whitney U hypothesis, for independent samples, obtaining a value _x000D_ of 0.023 that was lower than the value of alpha (0.05), so it is concluded that the application of _x000D_ the cooperative games program improved the school life.